High-performance ternary organic solar cells with thick active layer exceeding 11% efficiency. Issue 4 (8th February 2017) - Gasparini, Nicola; Lucera, Luca; Salvador, Michael; Prosa, Mario; Spyropoulos, George D.; Kubis, Peter; Egelhaaf, Hans-Joachim; Brabec, Christoph J.; Ameri, Tayebeh
Abstract : We present a novel ternary organic solar cell with an uncommonly thick active layer (∼300 nm), featuring thickness invariant charge carrier recombination and delivering 11% power conversion efficiency (PCE). Abstract : We present a novel ternary organic solar cell with an uncommonly thick active layer (∼300 nm), featuring thickness invariant charge carrier recombination and delivering 11% power conversion efficiency (PCE). A ternary blend was used to demonstrate photovoltaic modules of high technological relevance both on glass and flexible substrates, yielding 8.2% and 6.8% PCE, respectively.